2020
DOI: 10.1134/s074204632005005x
|View full text |Cite
|
Sign up to set email alerts
|

A Joint Study of Seismicity and SAR Interferometry Observations for Assessing the Possibility of an Eruption of the Dormant Bolshaya Udina Volcano

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The Bolshaya Udina volcano can also serve as an example, when some researchers associated the observed seismic activity in 2017 with the possible uplift of magma to the reservoir under the Uda structure and, as a result, assumed a high probability of an imminent eruption. However, further analysis of the displacements of the area of aftershock activity in time and the displacement fields on the slopes of the volcano, obtained in the process of processing of SAR images, showed that seismic activation most likely accompanied the process of retreat and subsidence of the magmatic melt downward from the volcano [Senyukov et al, 2020].…”
Section: Grace-gnss Integrationmentioning
confidence: 99%
“…The Bolshaya Udina volcano can also serve as an example, when some researchers associated the observed seismic activity in 2017 with the possible uplift of magma to the reservoir under the Uda structure and, as a result, assumed a high probability of an imminent eruption. However, further analysis of the displacements of the area of aftershock activity in time and the displacement fields on the slopes of the volcano, obtained in the process of processing of SAR images, showed that seismic activation most likely accompanied the process of retreat and subsidence of the magmatic melt downward from the volcano [Senyukov et al, 2020].…”
Section: Grace-gnss Integrationmentioning
confidence: 99%